PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER ( NHT ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 014 GURUN PANJANG DUMAI - Daniah Ginting Daniah Ginting; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract., These researchers based on the lack of science learning IPA IV grade students of SDN 014 Gurun Panjang Dumai. Average science student learning IPA at the beginning of the data was 58.33. The design of this study was classroom action research that aims to improve the learning outcomes of SDN 014 fourth grade students of SDN 014 Gurun Panjang Dumai by implementing cooperative learning model Numbered Heard Together (NHT). This study was conducted in the month of March until mei 2014. The subjects were 014 fourth grade students of SDN Gurun Panjang Dumai length of the school year 2013/2014 the number of students 30. Average student learning outcomes in daily test cycle I was 67,67dan 79.17 on the second cycle. Classical completeness of students on daily test cycle I 66.67% and increased the daily test II to 90% classically been completed. For the first activity of cyclic teacher first meeting with scores of 62.5% and the second meeting of the first cycle to 70.8%. In the second cycle the first meeting scores of 87.5% and the value of the second cycle of meetings of II increased to 91.7%. For the first cycle of activities meeting students' scores which I diperoleh50%, and the second meeting of the first cycle to 66.7%. At the first meeting of the second cycle increased to 83.3% and at the second meeting of the second cycle increased to 91.6%. From these results it can be concluded that the application of cooperative learning model Numbered Heard Together (NHT) can improve learning outcomes  grade students IV SDN 014 Gurun Panjang Dumai. Keywords : Cooperative Learning Model Numbered type Heard Together (NHT), Learning Outcomes.